2013
DOI: 10.1002/rcm.6624
|View full text |Cite
|
Sign up to set email alerts
|

Condensed‐phase laser ionization time‐of‐flight mass spectrometry of highly energetic nitro‐aromatic compounds

Abstract: Direct analysis of explosive compounds has been performed by laser ionization. A large dependence of the resultant spectra on the laser energy was observed that might be useful for studies of fragmentation pathways. For forensic applications, two sampling procedures might allow the use of LIMS as a screening technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…However, this route based on the release of CN from the molecule should be clearly less signicant than route (5), based on the most favourable release of the NO 2 groups. 5 Again, the evidence provided by mass spectrometry on the presence of C + and NO + in our measurements 25 supports this alternative route.…”
Section: Resultssupporting
confidence: 73%
“…However, this route based on the release of CN from the molecule should be clearly less signicant than route (5), based on the most favourable release of the NO 2 groups. 5 Again, the evidence provided by mass spectrometry on the presence of C + and NO + in our measurements 25 supports this alternative route.…”
Section: Resultssupporting
confidence: 73%
“…The influence of other reactive (O 2 ) and inert (Ar, He) background gases on the characteristic emissions of the excited molecular species in plasmas of the same phase-condensed energetic nitro compounds was also examined. 245,246 The relative intensity of CN and C 2 emissions was observed to be directly related to the gas composition, which allowed conclusions concerning the main pathways involved in the generation of such emission species to be drawn. The authors confirmed that molecular species generated in noble gases (Ar or He) atmospheres originated from both direct fragmentation and atomic recombination in the plume of ablated material.…”
Section: Effects Of Surrounding Atmospherementioning
confidence: 97%
“…It will populate an excited state that can either couple to a reaction pathway, resulting [19]. Many investigations have been conducted concerning the mechanism of decomposition of explosives under laser irradiation [20][21][22].…”
Section: Laser-induced Time Of Flight Mass Spectroscopy Of Typical Enmentioning
confidence: 99%